Perceptions of land use and land cover analysed using geospatial data. (September 2022) - San Martin Saldias, Daisy; Aguayo, Liliana Guzman; Wallace, Luke; Reinke, Karin; McLennan, Blythe
Abstract: Considering how individuals perceive landscape is important when undertaking land management decisions. However, understanding how the community perceives a landscape is complex involving their experiences in that landscape, their lived experiences and other socio-cultural processes. One of the key challenges to understanding perception is linking the landscape properties to what is experienced when individuals interact with the landscape. Increasingly the use of geospatial data offers a tool for understanding the landscape and perceptions. This study compares satellite estimates of land use with the perceptions of the inhabitants of Yungay, Chile. Viewshed analysis is used to reconcile the differences seen in the satellite image cover estimates and those of the participants. It was found that restricting the cover estimate to the visible landscape, provided similar estimates of cover to those made by the participants. This varied between demographic groups. With differences between participants living in urban and rural settings particularly evident. Highlights: We compare satellite based estimates of LULC with estimates made by individuals. Viewsheds are used to determine landscape visibility influence on peoples perceptions. Estimates of some demographics was closer to visible landscape than others. Geospatial analysis offers important information for understanding landscape perception. Challenges remain in linking geospatial data to perceptions of landscape.